Celebration of the New Year in Ukraine during the Soviet and post-Soviet periods - Oleksandra Matyukhina (Łódzkie Studia Etnograficzne, 2022)
In the second half of the 20th and in the early 21st century, that is during the Soviet and post-Soviet periods, the New Year was – and it still remains – one of the main calendar holidays celebrated by the urban population in Ukraine. It can be said with confidence that it has become a focus of a variety of customs, traditions of its celebration, both borrowed from other holidays and newly formed, inherent only to this one holiday. The current paper deals with the changes in the traditions and rituals of celebrating the New Year in the second half of the 20th and early 21st century in Ukraine, and demonstrates that its status as the main winter calendar holiday pertaining to the transition from the old to the new annual cycle is still maintained. The specific pattern of the New Year celebration, i.e. the integral complex of customs, traditions and rituals characteristic of it, took shape in the 1950s–1960s and it has mostly survived to the present day. First of all, it retains the character of a family holiday and the decorated New Year tree, as well as abundant treats and gifts, are still its inherent attributes. At the same time, at the end of the 20th century, the New Year celebrations were enhanced with new forms, customs, and rituals; peculiarly, the revised and rethought European and Chinese rituals and symbols were included in the celebration system. They have greatly enriched the magical component of the New Year holidays, intended to conjure up a better coming year. The New Year’s Day maintains and develops its character as the main holiday of the period of transition from one calendar year to another. Such holidays have always been a part of the real life of society.